Asymmetric Differences in the Gray Matter Volume and Functional Connections of the Amygdala Are Associated With Clinical Manifestations of Alzheimer’s Disease - Wu, Xingqi; Wu, Yue; Geng, Zhi; Zhou, Shanshan; Wei, Ling; Ji, Gong-Jun; Tian, Yanghua; Wang, Kai (Frontiers in Neuroscience, 2020)
Objective: Asymmetry is a subtle but pervasive aspect of the human brain, which may be altered in several neuropsychiatric conditions. Magnetic resonance imaging (MRI) studies have reported that cerebral structural asymmetries are altered in Alzheimer’s disease (AD), but most of these studies were conducted at the region of interest level. At the functional level, there are few reports of resting state functional asymmetries based on functional MRI. In this study, we investigated lateral differences in structural volumes and strengths of functional connectivity between individuals with AD and healthy controls (HCs) at the voxel level. Methods: Forty-nine patients with AD and 32 matched HCs were assessed. Analysis of voxel-based morphometry (VBM) of gray matter volume was performed at the whole brain level to explore anatomical cerebral asymmetries in AD. We then performed a seed-to-whole brain functional connectivity (FC) analysis to reveal FC asymmetries in AD. An asymmetry index (AI) was used to measure these changes, and the relationship between the structural and functional AIs and clinical symptoms of AD was explored. Results: VBM analysis revealed rightward and leftward lateralization in the amygdala and thalamus, respectively, in patients with AD. FC between the amygdala and the precuneus showed rightward lateralization in AD, which was the opposite of the lateralization in the HCs. Asymmetric changes in structure and function were associated with disease severity and functional impairment in AD. Conclusion: Our study highlights the value of considering asymmetries in the amygdala and thalamus in clinical evaluations and their relevance to clinical measures.